O Fundef na Educação do Estado do Pará: feitos e fetiches - Rosana Maria Oliveira Gemaque (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
The text presents an analysis of the effects of FUNDEF in the education of the State of Pará, evidenced in the state system of education, with the objective of evaluating the pertinence of the mechanisms of redistribution of the financial resources of that Fund, in relation to the: (i) reduction of the disparities in the expense-student in the state; (ii) enlargement of the capacity of registration offer for the municipal districts (iii) focalization of the resources in the fundamental teaching. For that, it presents the legal aspects of FUNDEF in the State of Pará; its composition and redistribution for government's sphere; their effects in the service to the Basic Education; relationship between the offer of registrations and financial capacity of government's spheres.